Insights into perceived listening difficulties post COVID-19 infection: no measurable hearing difficulty on clinical tests despite increased self-reported listening effort - Alhanbali, Sara; Alkharabsheh, Ana'am; Alanati, Wafa'a; Joudeh, Khader; Munro, Kevin J. (Frontiers in Neurology, 2023)
Objective The aim was to use a battery of clinic-based auditory assessment procedures to compare participants with and without self-reported hearing difficulties following a confirmed COVID-19 infection. A further aim was to compare the groups on self-reported measures of listening effort and fatigue. Methods There were 25 participants in each group (age range 20–59 years, 80% females). Participants were recruited after a minimum of 4 weeks of testing positive. Hearing assessment involved tympanometry, acoustic reflex thresholds, pure-tone audiometry (PTA; 0.25–14 kHz), and distortion product otoacoustic emissions (DPOAEs; 0.5–10 kHz). Listening effort was assessed using the Arabic version of the Effort Assessment Scale (EAS-A) and fatigue was assessed using the Arabic version of the Fatigue Assessment Scale (FAS-A). Results There was no difference between groups on any measure except for greater self-reported listening effort in the perceived hearing difficulty group (p = 0.01). Conclusion The only difference between groups was self-reported listening effort. This could be due to a subclinical auditory deficit following COVID-19, increased listening effort due to the impact of COVID-19 on cognitive processes, or a psychosomatic response/health anxiety.